Databases theory and applications : 28th Australasian Database Conference, ADC 2017, Brisbane, QLD, Australia, September 25-28, 2017, Proceedings /: 28th Australasian Database Conference, ADC 2017, Brisbane, QLD, Australia, September 25-28, 2017, Proceedings. (2017) - Unknown
No abstract available